Yes you do...You already have the equality of "y"......ergo...

Yes you can

Y= 2X+10 and in second equation Y=-2X-6

then we can put the value of Y in second equation

therefore 2X+10=-2X-6

=> 2X+2X= -6-10 { sign change because we move the numbers from left to right and right to left}

=> 4X= - 16

=> X= -16/4

=> X = -4

Hope this helps

Y= 2X+10 and in second equation Y=-2X-6

then we can put the value of Y in second equation

therefore 2X+10=-2X-6

=> 2X+2X= -6-10 { sign change because we move the numbers from left to right and right to left}

=> 4X= - 16

=> X= -16/4

=> X = -4

Hope this helps